👤

Bonjour j'aimerais de l'aide pour cet exercice de développement et réduction merci d'avance :

développer et réduire

A ( x ) = x – ( 2 x + 3 ) – ( 5 x – 1 ) + ( 3 x – 2 ) – x
B ( x ) = ( x – 2 ) x + 3 – 5 ( x – 1 ) + 3 x – ( 2 – x )
C ( x ) = ( x – 2 )( x + 3 ) – ( 5 x – 1 ) + ( 3 x – 2 )( – x )
D ( x ) = x – ( 2 x + 3 ) – 5 x ( – 1 + 3 x ) – ( 2 – x )
E ( x ) = ( x – 2 ) x + ( 3 – 5 x ) – ( 1 + 3 x )( – 2 – x )


Répondre :

bonjour

a (x) = x - 2 x - 3 - 5 x + 1 + 3 x - 2 - x
a(x) = - 4 x  - 4 

b(x) = x² - 2 x + 3 - 5 x + 5 + 3 x - 2 + x
b(x) = x² - 3 x + 6 

c(x) = x ² + 3 x - 2 x - 6 - 5 x + 1 - 3 x² + 2 x 
c(x) = - 2 x² - 2 x - 5

d(x) = x - 2 x - 3  + 5 x - 15 x² - 2 + x
d(x) = - 15 x² + 5 x - 5

e(x) = x² - 2 x + 3 - 5 x - ( - 2 - x - 6 x - 3 x²)
e(x) = x² - 2 x + 3 - 5 x + 2 + x + 6 x + 3 x²
e(x) = 4 x² + 5